Brain morphology of patients with body dysmorphic disorder - Atmaca, Murad; Bingol, Ismet; Aydin, Ayse; Yildirim, Hanefi; Okur, Ihsan; Yildirim, M. Alpagan; Gurok, M. Gurkan (Elsevier, 2010)
Background: There has been dearth of investigations concerning morphometric magnetic resonance imaging (MRI) study of regional brain volumes in body dysmorphic disorder (BOO). So we performed a volumetric MRI study in patients with BOO focusing on the in vivo neuroanatomy of thalamus, caudate nucleus, anterior cingulate cortex, and orbito-frontal cortex (OFC) concurrently. Methods: The whole brain, total gray and white matter volume, thalamus, caudate nucleus, anterior cingulate cortex, and OFC volumes were blindly measured in 12 unmedicated male BDD patients not having any comorbidity and 12 male control subjects matched for age, and gender. Results: The mean OFC and anterior cingulate volumes were significantly smaller than those of healthy controls. The mean white matter volume was larger than that of controls. There was a trend toward increased thalamic volume in patients compared with that of control subjects. Length of illness was inversely correlated with OFC volumes in the patient group both on the left and right sides. Conclusions: These findings may be interpreted as further evidence for the inclusion of BDD among a group of obsessive-compulsive spectrum disorders. Future research is necessary to confirm these preliminary findings, to extend them, and to clarify their significance with respect to the etiology and pathophysiology of BDD. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Body Dysmorphic Disorder; MRI; Orbito-frontal Cortex; OCD; Cingulate